(untitled) (Ameghiniana, 2008)
The fossil xenarthrans include giant forms, the ground sloths (Tardigrada), characteristic of the mammal fauna of the Pleistocene of South America. Although most authors agree in considering them as herbivorous, these forms have not been studied in terms of detailed morpho-functional analyses of their masticatory apparatuses. The aim of this work is the study the masticatory apparatus of the large Pleistocene ground sloths Glossotherium robustum, Lestodon armatus, Mylodon darwini and Scelidotherium leptocephalum (Mylodontidae) applying biomecanichal and morphogeometrical methods, and to compare with the information obtained for Megatherium americanum (Megatheriidae). The results are integrated with recent ecomorphological analyses that include three variables (hypsodonty index, dental occlusal surface area and relative width and shape of the muzzle) providing useful information for the inference of dietary habits and to propose a niche partitioning among these species. Glossotherium robustum and Lestodon armatus, the wide-muzzled sloths, were mostly bulk-feeders (i.e. ingest great amounts of food with each bite; probably grass and herbaceous plants). Mylodon darwini and Scelidotherium leptocephalum, the narrow-muzzled sloths, were mixed or selective-feeders (i.e. select plants or plant parts; grass and/or tree and shrubs foliage). The tooth design of mylodontids indicates that teeth were used mainly for crushing and grinding turgid and fibrous items respectively. Megatherium americanum was probably the most selective feeder among these sloths, and selectively fed on particular plants (shrubs) or plant parts (leaves, twigs, fruits). Its dentition was designed mostly for cutting soft but tough items which might include flesh, leaving open the possibility of an omnivorous diet.